Pre‐school child blood lead levels in a population‐derived Australian birth cohort: the Barwon Infant Study. Issue 4 (24th November 2019) - Symeonides, Christos; Vuillermin, Peter; Sly, Peter D; Collier, Fiona; Lynch, Victoria; Falconer, Sandra; Pezic, Angela; Wardrop, Nicole; Dwyer, Terence; Ranganathan, Sarath; Ponsonby, Anne‐Louise B
Abstract: Objectives: To investigate blood lead levels in an Australian birth cohort of children; to identify factors associated with higher lead levels. Design, setting: Cross‐sectional study within the Barwon Infant Study, a population birth cohort study in the Barwon region of Victoria (1074 infants, recruited June 2010 – June 2013). Data were adjusted for non‐participation and attrition by propensity weighting. Participants: Blood lead was measured in 523 of 708 children appraised in the Barwon Infant Study pre‐school review (mean age, 4.2 years; SD, 0.3 years). Main outcome measure: Blood lead concentration in whole blood (μg/dL). Results: The median blood lead level was 0.8 μg/dL (range, 0.2–3.7 μg/dL); the geometric mean blood lead level after propensity weighting was 0.97 μg/dL (95% CI, 0.92–1.02 μg/dL). Children in houses 50 or more years old had higher blood lead levels (adjusted mean difference [AMD], 0.13 natural log units; 95% CI, 0.02–0.24 natural log units; P  = 0.020), as did children of families with lower household income (per $10 000, AMD, –0.035 natural log units; 95% CI, –0.056 to –0.013 natural log units; P  = 0.002) and those living closer to Point Henry (inverse square distance relationship; P  = 0.002). Associations between hygiene factors and lead levels were evident only for children living in older homes. Conclusion: Blood lead levels in our pre‐school children were lower than in previous Australian surveys and recent surveys in areas at risk of higher exposure, and no children had levels above 5 μg/dL. Our findings support advice to manage risks related to exposure to historical lead, especially in older houses.